2002
DOI: 10.1051/0004-6361:20020116
|View full text |Cite
|
Sign up to set email alerts
|

Pristine CNO abundances from Magellanic Cloud B stars

Abstract: Abstract. We present chemical abundances for four main sequence B stars in the young cluster NGC 2004 in the Large Magellanic Cloud (LMC). Apart from H ii regions, unevolved OB-type stars are currently the only accessible source of present-day CNO abundances for the MCs not altered by stellar evolution. Using UVES on the VLT, we obtained spectra of sufficient resolution (R = 20 000) and signal-to-noise (S/N ≥ 100) to derive abundances for a variety of elements (He, C, N, O, Mg and Si) with NLTE line formation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
102
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 28 publications
14
102
2
Order By: Relevance
“…The chemical diffusion process is then dominated by magnetic diffusion, resulting in too strong mixing, incompatible with the observations. The data points show data of [13] (circles), [14] (triangles), [15] (upsidedown triangles) and [16] (diamonds). The grey box indicates data that will become available soon [9, in preparation].…”
Section: The Modelsmentioning
confidence: 99%
“…The chemical diffusion process is then dominated by magnetic diffusion, resulting in too strong mixing, incompatible with the observations. The data points show data of [13] (circles), [14] (triangles), [15] (upsidedown triangles) and [16] (diamonds). The grey box indicates data that will become available soon [9, in preparation].…”
Section: The Modelsmentioning
confidence: 99%
“…These studies include those of Lennon et al (1997), Gies & Lambert (1992), Kudritzki et al (1999), McErlean et al (1999) and Repolust et al (2004) in our Galaxy, Fitzpatrick & Bohannan (1993), Puls et al (1996), Dufton et al (2000), Korn et al (2002), Trundle et al (2004Trundle et al ( , 2005 and Venn (1999) for the Magellanic System, Venn et al (2000a), Smartt et al (2001) and Trundle et al (2002) for M 31, Monteverde et al (1997Monteverde et al ( , 2000 and Urbaneja et al (2003) for M 33 and Kaufer et al (2004), Urbaneja et al (2003) and Venn et al (2001Venn et al ( , 2000b for other Local Group galaxies. Studies of the progenitor O-type stars (see Bouret et al 2003;Hillier et al 2003;Heap et al 2004) and B-type giants (see Korn et al 2002, Lennon et al 2003 have also provided relevant observations to aid our understanding of the evolution of the surface chemical composition of early-type stars.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the progenitor O-type stars (see Bouret et al 2003;Hillier et al 2003;Heap et al 2004) and B-type giants (see Korn et al 2002, Lennon et al 2003 have also provided relevant observations to aid our understanding of the evolution of the surface chemical composition of early-type stars.…”
Section: Introductionmentioning
confidence: 99%
“…Composition values relative to PSC values given by de Boer (1991) for the Large Magellanic Cloud (LMC) and Small Magellanic Cloud (SMC) are fO=Hg $ 0:3 2 and fN=Og $ 0:3. Recently, Korn et al (2002) reported for the LMC an even lower nitrogen abundance, i.e., fN=Og $ 0:2. Some data on the isotopic abundances of carbon, nitrogen, and oxygen in dwarf galaxies have been published.…”
Section: Infall Of External Materials Into the Galactic Diskmentioning
confidence: 99%